국내 중등증 의료서비스 제공 방법에 대한 전문가 의견 조사: 포커스 그룹 인터뷰와 델파이 조사를 활용하여 - 박유신; Yu Shin Park; 장예슬; Ye Seul Jang; 허경덕; Kyungduk Hurh; 임재혁; Jae Hyeok Lim; 김세라; Sera Kim; 김영삼; Young Sam Kim; et al. (HIRA Research, 2024)
Background: With the increasing and diverse demand for critical care services in Korea, providing appropriate medical services to patients is becoming challenging due to limited resources. Consequently, a healthcare delivery system needs to be developed for effectively managing patients with severe and moderately severe conditions. Methods: Focus group interviews were administered using the Delphi survey questionnaire. The focus group comprised three nurses and three physicians working in critical and intermediate care units. For the Delphi survey, 15 experts who had substantial experience in and consideration of healthcare policies and systems related to critical care were recruited. The survey was conducted in two rounds. Results: Key findings in providing medical services for patients requiring intermediate levels of care in Korea are summarized as follows. First, the need for an independent ward dedicated to close monitoring of moderately severe patients is required. Second, intermediate care units should cater to a wide range of conditions rather than being limited to specific disease groups. Third, intermediate care units are crucial for independent operation, with their own staffing standards and necessary equipment. Fourth, limiting the operation of intermediate care units as well as the number of beds was proposed for healthcare facilities capable of maintaining quality control. Fifth, there was consensus that the admission criteria for intermediate care units should be established to ensure their appropriate utilization. Conclusion: This study imparts critical insights into the demand for and approaches to healthcare delivery systems for patients needing intermediate levels of care using critical care resources, offering evidence to enhance efficiency.